Determination of amoxicillin: A penicillin antibiotic in pharmaceutical dosage samples by spectrophotometric method - Pasha, Chand (Eclética Química, 2024)
New coupling agents such as 2,4-toluene diamine or sulphanilamide for the determination of amoxicillin spectrophotometrically are described. These methods are straightforward based on the reaction of amoxicillin with diazotized products of 2,4-toluene diamine or sulphanilamide to produce coloured azo dyes with maximum absorption at 462 or 468 nm. Amoxicillin responds linearly from 1.2–24.8 or 1.8–32.0 mg mL–1 when coupled with diazotized 2,4-toluene diamine or sulphanilamide. The molar absorptivity and Sandell’s sensitivity of amoxicillin with 2,4-toluene diamine or amoxicillin with sulphanilamide azo dyes were 3.307 × 104 or 2.632 × 104 L mol–1 cm–1 and 1.105×10-2 or 1.388×10-2 mg cm-2, respectively. The regression equation, correlation coefficient (R2), detection limit and quantitation limit of amoxicillin with 2,4-toluene diamine or amoxicillin with sulphanilamide were evaluated. The percentage recoveries ranged from 97.00 to 100.50 with a relative standard deviation value was ± 0.98 to ± 1.85%. The method does not need temperature control or solvent extraction and has been applied successfully to determine amoxicillin in pharmaceutical preparation (tablets).